PERBEDAAN STATUS GIZI DAN TINGKAT KESEGARAN JASMANI PADA ANAK SEKOLAH DASAR PERDESAAN DAN PERKOTAAN - Dian Ratna R; Dyah Umiyarni Purnamasari; Kusnandar Kusnandar (Kesmas Indonesia, 2015)
School age children 6-12 years require attention to meet the needs of nutrients in the body to achieve a balanced nutritional status. In addition to nutritional status, physical activity is also needed to increase physical activity by the bodyin order to perform daily activities. The difference of geographical location of domicile has an influence on eating patternand daily activities. This research aimed to know the difference of nutritional status and physical fitness level between rural and urban elementary school children in Banyumas district. The type of research used was descriptive quantitative with cross-sectional approach. Sampling used purposive sampling technique. Sample used was 52 students of class V elementary school. The data analysis used Independent sample t-test. Result showed category overweight of nutritional status for children in rural (11.5%) was lower than children in urban(38.5%). Conversely, physical fitness levelfor children in rural (57.7%) was higher than children in urban(15.4%). Conclusion: there were differences in nutritional status (p=0.02) and physical fitness level (p=0.00) on elementary school children in rural and urban areas. Suggestion: students are expected to increase physical activity outside of school hours in order to obtain good physical condition